Studies on the muscle strength around the elbow joint - Ishiko, T. (Association for the Scientific Studies on Judo, Kodokan, 1969)
The only Kansetsu-waza (joint technique) allowed in Judo is the joint lock of the elbow joint. This is due to the fact that the muscle strength around the elbow joint is neither too strong (if it is too strong, it is not possible to perform the joint lock, for example the hip joint) nor too weak (if it is too weak, it is dangerous, for example, the finger joints), and also the direction of joint movement is varied, and consequently, there is very little danger involved. This being the case, it is important from the kinesiologic point of view of measure muscle strength relating to the elbow joint when the joint is in various positions. However, there are certain difficulties encountered in the measurement of muscle strength in this region when the usual measuring instruments are used, and in order to overcome these difficulties a dynamometer suited to the purpose of the experiment was devised.